Nanoparticle-Based Drug Delivery Systems for Induction of Tolerance and Treatment of Autoimmune Diseases - Li, He; Yang, Yong-Guang; Sun, Tianmeng (Frontiers in Bioengineering and Biotechnology, 2022)
Autoimmune disease is a chronic inflammatory disease caused by disorders of immune regulation. Antigen-specific immunotherapy has the potential to inhibit the autoreactivity of inflammatory T cells and induce antigen-specific immune suppression without impairing normal immune function, offering an ideal strategy for autoimmune diseases treatment. Tolerogenic dendritic cells (Tol DCs) with immunoregulatory functions play important roles in inducing immune tolerance. However, effective generation of tolerogenic DCs in vivo remains a great challenge. The application of nanoparticle-based drug delivery system in autoimmune disease treatment can increase the efficiency of inducing antigen-specific tolerance in vivo. In this review, we discuss multiple nanoparticles, with a focus on their potential in treatment of autoimmune diseases. We also discuss how the physical properties of nanoparticles influence their therapeutic efficacy.